Recent Advances in Bioactive Compounds, Health Functions, and Safety Concerns of Onion (Allium cepa L.) - Zhao, Xin-Xin; Lin, Fang-Jun; Li, Hang; Li, Hua-Bin; Wu, Ding-Tao; Geng, Fang; Ma, Wei; Wang, Yu; Miao, Bao-He; Gan, Ren-You (Frontiers in Nutrition, 2021)
Onion (Allium cepa L.) is a common vegetable, widely consumed all over the world. Onion contains diverse phytochemicals, including organosulfur compounds, phenolic compounds, polysaccharides, and saponins. The phenolic and sulfur-containing compounds, including onionin A, cysteine sulfoxides, quercetin, and quercetin glucosides, are the major bioactive constituents of onion. Accumulated studies have revealed that onion and its bioactive compounds possess various health functions, such as antioxidant, antimicrobial, anti-inflammatory, anti-obesity, anti-diabetic, anticancer, cardiovascular protective, neuroprotective, hepatorenal protective, respiratory protective, digestive system protective, reproductive protective, and immunomodulatory properties. Herein, the main bioactive compounds in onion are summarized, followed by intensively discussing its major health functions as well as relevant molecular mechanisms. Moreover, the potential safety concerns about onion contamination and the ways to mitigate these issues are also discussed. We hope that this paper can attract broader attention to onion and its bioactive compounds, which are promising ingredients in the development of functional foods and nutraceuticals for preventing and managing certain chronic diseases.